Long-term outcomes of symptomatic optic pathway glioma: 32-year experience at a single Western Australian tertiary pediatric oncology center - Rajagopal, Revathi; Khan, Mumtaz; Lethbridge, Robert; Lee, Gabriel; Lee, Sharon; Dyke, Jason; Fabian, Vicki; McGrath, Alycea; Taylor, Mandy; Jacoby, Peter; Endersby, Raelene; Nagabushan, Sumanth; et al. (Frontiers in Oncology, 2023)
Introduction: Optic pathway gliomas (OPGs) are associated with significant risk of visual and endocrine morbidity, but data on long-term outcomes in symptomatic patients is sparse. This study reviews the clinical course, disease progression, survival outcomes and long-term sequelae in pediatric patients with symptomatic OPGs in our institution over three decades. Methods: Retrospective review of patients with symptomatic OPG treated in a single tertiary pediatric oncology center from 1984 to 2016. Results: A total of 37 patients were diagnosed with symptomatic OPG. Decreased visual acuity was the commonest presenting symptom (75.7%). Surgical intervention was performed in 62.2%; 56.1% underwent biopsy, 26.1% surgical debulking and 17.4%had orbital decompression with cystic fenestration and cosmetic optic nerve excision at different treatment intervals. CSF diversion was performed in 47.8% patients. Histopathologic examination confirmed 86% to be pilocytic astrocytoma and 1 ganglioglioma. 46% received chemotherapy and 48% had radiotherapy, at different intervals. Median follow-up was 13.74 years. In NF1 patients, overall survival (OS) was 100% at 5 years and 55.6±24.8% at 25 years while progression-free-survival (PFS) was 50±15.8% at 5 and 20 years. In non-NF1 patients, OS was 96.2±3.8% at 5 years and 87.4±9% at 25-years. 5-year PFS was 53.8 ±9.8% and 25-year PFS was 49.0±10%. Cumulative PFS was 53±8.3% at 5 years and 49.7±8.4% at 20 years while cumulative OS was 97.2±2.7% at 5 years and 77.5±10.8% at 25 years. 59.5% patients developed post-operative endocrinopathy. Long-term vision was normal in 8.1%, improved in 13.5%, stabilized in 40.5% but worsened in 37.8% patients. Three patients treated with radiotherapy developed second brain tumors. Conclusion: 25-year OS in this cohort was 77.5% but survivorship carried significant long-term morbidities including radiation-induced second malignant brain tumors.